An Update on the Management of Chronic Hepatitis C: Consensus Guidelines from the Canadian Association for the Study of the Liver - Robert P Myers; Alnoor Ramji; Marc Bilodeau; Stephen Wong; Jordan J Feld (Canadian Journal of Gastroenterology)
Chronic hepatitis C remains a significant medical and economic burden in Canada, affecting nearly 1% of the population. Since the last consensus conference on the management of chronic hepatitis C, major advances have warranted a review of recommended management approaches for these patients. Specifically, direct-acting antiviral agents with dramatically improved rates of virological clearance compared with standard therapy have been developed, and several single nucleotide polymorphisms associated with an increased probability of spontaneous and treatment-induced viral clearance have been identified. In light of this new evidence, a consensus development conference was held in November 2011; the present document highlights the results of the presentations and discussions surrounding these issues. It reviews the epidemiology of hepatitis C in Canada, preferred diagnostic testing approaches and recommendations for the treatment of chronically infected patients with the newly approved protease inhibitors (boceprevir and telaprevir), including those who have previously failed pegylated interferon and ribavirin therapy. In addition, recommendations are made regarding approaches to reducing the burden of hepatitis C in Canada.